Novel therapeutic compound tuftsin–phosphorylcholine attenuates collagen-induced arthritis. (4th February 2016) - Bashi, T; Shovman, O; Fridkin, M; Volkov, A; Barshack, I; Blank, M; Shoenfeld, Y
Summary: Treatment with helminthes and helminthes ova improved the clinical symptoms of several autoimmune diseases in patients and in animal models. Phosphorylcholine (PC) proved to be the immunomodulatory molecule. We aimed to decipher the tolerogenic potential of tuftsin–PC (TPC), a novel helminth-based compound in collagen-induced arthritis (CIA) a mouse model of rheumatoid arthritis (RA). CIA DBA/1 mice were treated with TPC subcutaneously (5 µg/0.1 ml) or orally (250 µg/0.1 ml), starting prior to disease induction. The control groups were treated with PBS. Collagen antibodies were tested by enzyme-linked immunosorbent assay (ELISA), cytokine protein levels by ELISA kits and regulatory T (Treg ) and regulatory B (Breg ) cell phenotypes by fluorescence-activated cell sorter (FACS). TPC-treated mice had a significantly lower arthritis score of 1.5 in comparison with control mice 11.8 ( P  < 0.0001) in both subcutaneous and orally treated groups at day 31. Moreover, histology analysis demonstrated highly inflamed joints in control mice, whereas TPC-treated mice maintained normal joint structure. Furthermore, TPC decreased the titres of circulating collagen II antibodies in mice sera ( P < 0.0001), enhanced expression of IL-10 ( P < 0.0001) and inhibited production of tumour necrosis factor (TNF)-α, interleukin (IL)−17 and IL-1β ( P < 0.0001). TPC significantly expanded the CD4 + CD25 + forkhead box protein 3 (FoxP3 + ) Treg cells and CD19 + IL-10 + CD5 high CD1d high T cell immunoglobulin mucin-1 (TIM-1 + ) Breg cell phenotypes ( P < 0.0001) in treated mice. Our data indicate that treatment with TPC attenuates CIA in mice demonstrated by low arthritic score and normal joints histology. TPC treatment reduced proinflammatory cytokines and increased anti-inflammatory cytokine expression, as well as expansion of Treg and Breg cells. Our results may lead to a new approach for a natural therapy for early rheumatoid arthritis onset.